Heat Treatment of Edible Bird's Nest to Fulfill Export Requirements to Canada - Umar Suryanaga; Rineke Sara (Greenation Publisher & Yayasan Global Research National, 2025)
The export requirements for swallow's nest (EBN) to Canada refer to the import procedure edible bird's nest (other than cooked canned commercially sterile) published by the Canadian Food and Inspection Agency (CFIA). One of the conditions is that the EBN is heated to a minimum temperature of 100 oC within a minimum of 1 hour. This study aims to test the heating treatment of EBN with a temperature of 100 °C for 1 hour according to the requirements of export to Canada and compare it with the requirements of the World Organization of Animal Health (WOAH). This researcher used clean EBN that had not been heated, coming from the island of Sumatra. The EBN sample was divided into four groups. The first group as a control, the second group heated 70 oC for 3.5 seconds, the third group heated 100 oC for 1 minute and the fourth group heated to 100 oC for 1 hour. The parameters tested in each group were sialic acid, physicochemical (water content, pH, water holding capacity (WHC), and water absorption index (WAI)). In addition, sensory attributes (color, taste, aroma, and texture) were also tested using panelists. The treatment of heating EBN at 100 °C for one hour causes protein denaturation that changes the functional properties of EBN. This treatment also reduces the developing power of EBN by up to 50% and has a significant influence on sensory and physicochemical properties, both color, taste, aroma, and texture. Heating EBN 100 °C for one hour reduces EBN quality, while EBN heating according to WOAH requirements i.e. heating 70 °C for 3.5 seconds does not affect EBN quality. Heating treatment of EBN 100 °C for one hour is not recommended.